Levitin-Polyak Well-Posedness of an Equilibrium-Like Problem in Banach Spaces - Ru-liang Deng (Abstract and Applied Analysis)
The concept of Levitin-Polyak well-posedness of an equilibrium-like problem in Banach spaces is introduced. Under suitable conditions, some characterizations of its Levitin-Polyak well-posedness are established. Some conditions under which an equilibrium-like problem in Banach spaces is Levitin-Polyak well-posed are also derived.